Mental well-being: A 16-year follow-up among older residents in Jyväskylä - Heikkinen, Riitta-Liisa; Kauppinen, Markku (Archives of gerontology and geriatrics, 2011)
This study investigated changes in perceived depression, anxiety and loneliness during a 16-year follow-up among elderly Jyväskylä residents born in 1914–1923. A further concern was with how perceived atmosphere in the formative environment was reflected in depression, anxiety and loneliness in old age. The first phase of the study took place in 1988 when interviews were conducted with 635 persons (241 men and 394 women). Depression and anxiety were assessed using the Finnish modified version of Beck's 13-item depression scale (RBDI), which was completed fully by 74% of the interviewees. Loneliness was assessed with a single four category item. In the second phase of the study in 1996, interviews were conducted with 410 persons, of whom 94% filled the RBDI questionnaire. In the third phase in 2004, the number of interviewees was 220 and the response rate 82%. There were no significant changes in the number of people with depressive symptomatology and anxiety, except in 1996 when the proportion of men with mild and moderate depression almost doubled. The number of men and women who felt lonely increased significantly during the 16-year follow-up. People who said they were lonely also had more depression and anxiety than others. People who had grown up in warm and safe environment were the most balanced mentally. The presence or absence of warmth and safety in the formative environment is reflected in mental well-being even at a very old age.